The role of social capital in a trust-building model between police and communities in the Ethekwini Metropolitan Municipality, South Africa - Mkhize, Mbekezeli Comfort (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.